A 10-Years Risk of Cardiovascular Disease Among HIV-Positive Individuals Using BMI-Based Framingham Risk Score in Indonesia. (January 2021) - Lindayani, Linlin; purnama, Heni; Nurhayati, Nunung; Sudrajat, Diwa Agus; Taryudi, Taryudi
Introduction: Cardiovascular disease (CVD) is the primary cause of death in HIV patients. The number of HIV patients suffering from cardiovascular disease is almost twice as high as that of patients who are not HIV-positive. Objective: The purpose of this study was to evaluate risk of cardiovascular disease among HIV-positive persons. Methods: We conducted a cross-sectional study with HIV positive individuals at public health center and non-AIDS govermental organization. We enrolled people diagnosed with HIV, age over 30 years old, and on CVD medications. We collected data of demographic, anthropometric and clinical information, smoking history, and non-fasting cholesterol and blood glucose. Estimation of 10-years CVD risk was calculated using the BMI-based Framingham Risk Score. Results: Of 150 participants enrolled, 66.7% were male and mean age was 38.09 (SD = 7.99) years. The mean current CD4 counts was 493.3 (SD = 139.8) cells/mm 3 . Female were younger, had a shorter duration living with HIV and a shorted duration of receiving ART than males. About 8.7% of respondents had a high risk of developing a CVD event in the next 10 years, and higher among females than males. The most common CVD risk factors were smoking, high blood pressure, and hypercholestrolemia. Conclusion: Our study demonstrates that HIV positive persons who are at risk for developing CVD in the next 10-years. There is an increasing need for educational programs on CVD prevention for the HIV-positive person and to further facilitate the identification of persons at elevated risk in routine practice.